Interrogation of children in conflict with the law: A comparative analysis between Malaysian law and the international standards - Asril Amirul, Zakariah; Aminuddin, Mustaffa; Mohd Badrol, Awang; Nazli, Ismail@Nawang; Mohd Lotpi, Mohd Yusob (2018)
Interrogation is considered as one of the crucial stages of juvenile justice process. During the process of interrogation, any suspected child may be subjected to various modes of questioning, interview and examination with a purpose to obtain evidence and confession for an alleged crime. While this process undeniably important aspect of criminal process aims to maintain public order and justice, it may turn out to be a terrifying event for children, who are known for their physical and emotional vulnerability. This paper aims to comparatively analyse between Malaysian current law and practice an interrogation of children and the international standards set by the international instruments. It attempt to examine to what extent current Malaysian law on interrogation measure up with the recommendation for the reform of current Malaysian law on interrogation measure up with the requirements of international standards. This article concludes with the recommendation for the reform of current Malaysian law and practices on interrogation of children.